Cyclo-oligomerization of hydroxyl-containing mono-functional benzoxazines: a mechanism for oligomer formation. Issue 13 (18th March 2020) - Zhen, Hecheng; Yang, Huiyun; Wang, Mei; Lu, Guosheng; Liu, Yanfang; Run, Mingtao
Abstract : The oligomerization of mono-functional benzoxazines is demonstrated with intermolecular cyclization via a Mannich bridge structure as the primary reaction pathway. Abstract : The oligomerization of mono-functional benzoxazines is demonstrated with intermolecular cyclization via a Mannich bridge structure as the primary reaction pathway. The structures of oligomers of mono-functional benzoxazines were previously thought to be benzoxazine dimers stabilized by inter- and intramolecular hydrogen bonding. This study is based on four hydroxyl-containing mono-functional benzoxazines synthesized from phenol, o -allylphenol, o -cresol, p -cresol, diglycolamine, and paraformaldehyde. A reaction mechanism is proposed that ortho - and para -substituted-phenol-based mono-functional benzoxazines undergo thermally activated ring-opening cyclo-oligomerization (ROCO) and ring-opening oligomerization (ROO), whereas their phenol-based counterpart polymerizes into polybenzoxazine following ROCO and ROO, which is evidenced by the data of 1 H and 13 C nuclear magnetic resonance spectra, Fourier transform infrared spectra, size exclusion chromatograms, and mass spectra of thermally treated samples.